Alcune considerazioni sull’uso della traduzione nella didattica d’italiano come lingua straniera - Paleta, Alicja (Studia Romanica Posnaniensia, 2013)
For many years, the translation has not been recommended and has even been banned in language teaching and learning. Recently, it seems to regain some success at this field. In this article we briefly analyze how the role of this technique has changed throughout the years within the major language teaching theories so as to get to the reasons for its reassessment we can observe nowadays. Finally, we present some considerations on how we can use activities based on translation in the classroom with a particular regard to Italian language teaching to adult learners who are native speakers of Polish.